2019
DOI: 10.14267/cjssp.2019.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A look at Lesotho government and NGOs' economic empowerment programs with respect to rural poverty reduction

Abstract: This study examined ongoing economic empowerment programs that are being implemented by both government and NGOs in rural areas of Lesotho. The key objectives were to gain some insight into major government and NGO poverty reduction programs that target or at least include the rural poor, and to establish the challenges encountered by the benefactors in executing their poverty reduction efforts. A qualitative approach involving interviews was utilized to collect data from a sample of six government ministries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Evidence of this interference was most notable when it came to shortlisting or selecting beneficiaries for funding or training programs. In Lesotho, interference from political leadership was also found to be a problem incapacitating poverty reduction programmes (Hapazari & Hapazari, 2019). In the case of Zimbabwe, the ZANU PF party was equally blamed during the interviews for demanding that its loyal followers be given all the opportunities.…”
Section: Political Interferencementioning
confidence: 99%
“…Evidence of this interference was most notable when it came to shortlisting or selecting beneficiaries for funding or training programs. In Lesotho, interference from political leadership was also found to be a problem incapacitating poverty reduction programmes (Hapazari & Hapazari, 2019). In the case of Zimbabwe, the ZANU PF party was equally blamed during the interviews for demanding that its loyal followers be given all the opportunities.…”
Section: Political Interferencementioning
confidence: 99%
“…(Abdul Latif, 2015, p. 956) Therefore, the Ministry of Social Development, through the General Administration of Social Protection, implements the economic empowerment program, which aims to reduce poverty, empower the poor, and reaching a degree of reliance on themselves and improve their quality of lif. and many studies have dealt with the issue of economic empowerment and improving the quality of the poor, including the study (Innocent 2019) The study aimed to analyze the poverty reduction programs of the major governmental and non-governmental organizations targeting the rural poor in Lesotho (Southern Africa) and identifying the challenges that beneficiaries face in implementing their poverty reduction efforts Where the study revealed that various economic empowerment programs have been implemented throughout across the country Where the study revealed that various economic empowerment programs have been implemented throughout the country, and one of the main challenges was faced by the government and nongovernmental organizations to seeking the poor helping process in rural areas is the Weakness of resources and its limitations, insufficient cooperation between institutions and weak participation of the target the study (Adaileh 2019): The study aimed to identify the social, economic and subjective dimensions of small projects on the Jordanian family and to identify the obstacles that families face in implementing small projects The results of the study revealed that the social dimensions the borrowers is achieve from establishment small projects are its high contribution to enhancing their social status among their families and local communities As for the economic dimensions, they were represented in thinking of expanding the project to increase profit return and the experience in marketing the project's , and for the self-dimensions, the results confirmed the role and effectiveness of the projects in improving the conditions of the beneficiaries of the Productive Families Program in terms of increasing their independence and selfreliance and enhancing their self-confidence.…”
Section: Introductionmentioning
confidence: 99%
“…The overall high literacy rate in Lesotho of around 90% probably means that successive governments have made efforts to provide education to their people [ 3 , 4 ]. Nonetheless, the country faces dwindling local market due to entrepreneurs and skilled labour scarcity [ 5 ]. Lesotho currently has high youth unemployment rate of about 45 to 50% [ 6 ], resulting in poverty and economic stagnation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%